Stories of lost souls - Knightley, Keira, 1985-; Blanchett, Cate, 1969-; Bettany, Paul, 1971-; Jackman, Hugh; Gandolfini, James; Boyd, Billy, 1968-; Sterling Entertainment Group; America Video Film (Fort Mill, SC : Sterling Entertainment Group, 2005)
"Confronted with tragic and mysterious circumstances, six varying personalities from different walks of life must come to terms with the bizarre twists their lives have taken. From an abusive alcoholic husband (Gandolfini) to a seductive temptress at a New Year's Eve party (Knightley) to debonair swindler (Bettany), all of the characters share one common element - the desperation for redemption felt by all those who live in the realm of Lost Souls."-- Container
Euston Road -- Standing room only -- New Year's Eve -- Bangers -- Whole new day -- Sniper 470
"Warning: Contains mature language and content. May not be suitable for all audiences."-- Container
Bonus features: filmographies, biographies, scene access, interactive menus
Keira Knightley, Cate Blanchett, Paul Bettany, Hugh Jackman, James Gandolfini, Billy Boyd
DVD, Region 1 ; Dolby digital stereo
UNCP 324545 - gift
Keywords: Feature films